Grinding induced catalyst free, multicomponent synthesis of Indoloindole pyrimidine. Issue 41 (8th October 2020) - Maury, Suresh Kumar; Kumari, Savita; Kushwaha, Ambuj Kumar; Kamal, Arsala; Singh, Himanshu Kumar; Kumar, Dhirendra; Singh, Sundaram
Graphical abstract: Highlight: Liquid assisted hand grinding. Pure product without column chromatography. High yield. Metal free synthesis. Abstract: A simple, efficient, environmentally friendly, and ethanol assisted mechanochemical approach for the synthesis of Indoloindole pyrimidine has been developed through a simple mortar and pestle under catalyst-free grinding method. The present protocol is green and associated with easy workup step, high yield of product, short reaction time, and bear an extensive range of functional groups.